Investigation on Materials Compatibility Using Nanoparticles Additive in Refrigerating System - Bi Shengshan; Shi Lin; Yong Hanlin; Wang Ruixiang (Zhileng xuebao, 2006)
The compatibility of refrigerating system materials with HFC134a/mineral oil(MO) and HTR02/mineral oil appended with Nanoparticle TiO_2 and SiO_2 was experimentally studied using the alternative materials compatibility research method accepted internationally.The result indicates that HFC134a/MO/nanoparticles and HTR02/MO/nanoparticles are compatible with the refrigerator materials,and the nanoparticle can reduce the negative effect on the compatibility caused by the poor solubility between the HFC and mineral oil.